"Man, Have I Got a Story for You": Facilitated Autoethnography as a Potential Research Methodology in Human Resource Development. (September 2016) - Grenier, Robin S.; Collins, Joshua C.
Despite the potential value of narratives to inform and change workplace culture and practice, many stories from individuals at the margins of organizations often go untold or unheard. Based on a methodological framework of existing narrative approaches—autoethnography, guided autobiography, and narrative inquiry—we present in this article a new, emerging methodology: facilitated autoethnography (FAE). We suggest that FAE has the potential to offer human resource development (HRD) scholars and practitioners a new approach for exploring, collecting, and disseminating workplace narratives to a broad audience. The article concludes with a discussion of the emerging methodology and potential implications for its application in the field of HRD.